2015
DOI: 10.1007/s13197-015-1789-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant and antibacterial properties of Bene (Pistacia atlantica subsp. mutica) hull essential oil

Abstract: The tree Pistacia atlantica subsp. mutica, namely Bene, is widely distributed in Iranian mountains. Recent studies revealed that the oil of Bene was stable, even more stable than sesame oil, with antioxidant properties. This can give versatile applications for the oil. The volatile composition of this oil has not chemically been investigated so far. In this study, sixty three compounds were identified in the essential oil (EO) of Bene hull. The major components were determined to be α-pinene (20.8 %), camphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…The cuvettes were thermostated at 50°C between measurements. The average percent of inhibition was calculated by the following formula [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…The cuvettes were thermostated at 50°C between measurements. The average percent of inhibition was calculated by the following formula [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…α-Pinene was reported as major constituents of Pistacia atlantica resin oil and has very low toxicity [10]. Rezaie and coworkers have demonstrated that Pistacia atlantica hull oil has free radical scavenging activity which was comparable to α-tocopherol in vitro, and this confirmed that Pistacia atlantica acts against oxidative stress [26]. Finally, consistent with these studies we showed that Pistacia atlantica resin oil has potent antioxidant activity and also we showed that antioxidant capacity of Pistacia atlantica resin oil in diabetic model is still present which was not reported before.…”
Section: Resultsmentioning
confidence: 90%
“…have reported that P. atlantica oil has remarkable antioxidant activities compared with positive control. 14 Koizumi et al . showed that severe burn damage cause promotion of free radicals which in turn result in vasodilatation and SOD can act as a protective factor against vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Also other studies reported antimicrobial activity of P. atlantica oil. 14 , 25 Therefore, P. atlantica resin oil in addition to increase antioxidants also has antimicrobial properties and it reduce the chance of infection and accelerate the process of wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation